Between Renaissance and Baroque: a study of the keybord works of Frescobaldi - Maske, H H (Rhodes University, Faculty of Humanities, Department of Music, 1963)
The present study is an attempt to enlarge upon the proposition that the age of Frescobaldi was, like all others, an age of transition, in his case the transition from Renaissance to Baroque. His position within this change is central, both in time and importance. In our first two chapters, the various categories of keyboard works which he enriched will be considered, with their prehistories, his contributions, and analyses of individual pieces. In chapter I the works mainly of instrumental origin will be dealt with, and in chapter ll those of more vocal derivation. In the final chapter, the information thus gleaned will be used to demonstrate his exact position within the transition, particularly with regard to its two most important aspects, the harmonic field and the interaction of vocal and instrumental elements.
Keywords: Frescobaldi, Girolamo; 1583-1643 -- Keyboard instrument music; Frescobaldi, Girolamo, 1583-1643 -- Criticism and interpretation; Music -- Italy -- 17th century; Organ music -- History and criticism; Keyboard instrument music -- 17th century -- History and criticism